Derrida, Terrorism, and Communism: A Comment on "Autoimmunity: Real and Symbolic Suicides” - David-West, Alzo (Cosmos and History: The Journal of Natural and Social Philosophy, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:none; mso-layout-grid-align:none; text-autospace:none; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-fareast-language:#00FF;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> This essay makes an appraisal of the political articulations of the late Jacques Derrida in his "Autoimmunity: Real and Symbolic Suicides” interview as a starting point for evaluating him as a political philosopher. Derrida having claimed in the past that he was convinced of Marxism, a critical comparison serves to illustrate where his radical-sounding pronouncements stand in relation to the Marxist perspective. Derrida turns out to be unremarkable, expounding an ambiguous and eclectic pre-Marxist prophetism.